TOURISM DEPARTMENT STRATEGY OF PRESERVING ART AND CULTURE IN MEDAN CITY AT GELAR MELAYU SERUMPUN EVENT (GeMeS) - Hafiza Azura; Wan Anayati (Universitas Negeri Medan, 2021)
The objective of this thesis are: to find out the implementation of the persuasive language used in the promotion strategy of Gelar Melayu Serumpun (GeMeS), and to find out the persuasive language occure in Gelar Melayu Serumpun (GeMeS). The research design used in this study is descriptive qualitative method. The data analysis of this thesis are library research, brochures, articles , invitation letters and social media. The data used in this study are the persuasive language of the Medan City Tourism Office as the organizer of the GeMeS event totaling three informant. The informant as the employee of Medan City Tourism Office is needed to complete the data. The persuasive language carried out by the GeMeS event organizers occure by distribusing various form of promotional media such as brochures, articles, invitation letters and social media. Medan City Tourism Office.The result showed that the implementation of the persuasive language used in the promotion strategy of the Serumpun Malay title (GeMeS) was divided into three parts, namely advertising persuasion, propaganda persuasion, and education persuasion.Keywords: Strategy, Promotion, Arts and Malay Culture, and Persuasion Language.